AI-Counsellor Using Emerging Technique (International Journal of Scientific Research in Science and Technology, 2024)
Mental health is an integral part of overall well-being, encompassing emotional, psychological, and social well-being. It affects how we think, feel, and act. Yet, mental health concerns are on the rise globally. According to the World Health Organization (WHO), an estimated one in four people will experience a mental health condition in their lifetime. Depression, anxiety, and stress are amongst the most prevalent mental health issues. This paper aims to develop an AI Counsellor - a chatbot designed to use AI and ML capabilities to offer initial mental health support. Design the chatbot to understand user input effectively through sentiment analysis, intent recognition, and entity recognition. Finally develop a user-friendly interface for text-based interaction with the AI-Counsellor.